Pelibatan Masyarakat dalam Pengelolaan Situs Gunung Wingko, Bantul - Anggraeni Anggraeni (Faculty of Cultural Sciences, 2018)
Archaeological researches at Gunung Wingko Site, Kecamatan Sanden, Bantul, had been conducted formore than 40 years ago. Nevertheless, the results of observations, interviews, Focus Group Discussions(FGD), and archaeological exhibition on Sanden Fair 2018 indicate that the existence and the culturalsignifcance of the site had only been known by certain communities. Local people unawareness of theexistence and the cultural signifcance of the site had so far caused site damage. Terefore, a number ofaction plans have been suggested during the FGD that involved the local people and some institutionsrelevant to the case of Gunung Wingko, and have to be done as soon as possible to prevent the sitefrom further damage. Te plans comprise dissemination of the site values, the establishment of thesite as cultural heritage (Cagar Budaya), site management, and the development of a site informationcenter. Tis center could be integrated with other tourist destinations which have been establishedaround the site. In this case, local people should be involved in preparing material displayed in theGunung Wingko Site Information Center.